2017
DOI: 10.1089/met.2017.0074
|View full text |Cite
|
Sign up to set email alerts
|

Browning of Abdominal Aorta Perivascular Adipose Tissue Inhibits Adipose Tissue Inflammation

Abstract: Our study demonstrated that browning of aPVAT in HFD-fed rats lowered the pro-inflammatory adipokine expression levels and activated AMPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…Chromium appears to have a negligible effect on olanzapine-increased food intake, indicating there’s a possibility of increased energy expenditure as an explanation for the improvement in weight gain. Increasing evidence indicates that an increased expression of UCP-1 in white adipose tissues represents an alternative mechanism for the improvement of metabolic impairment via energy expenditure [35]. Here, we found that chromium not only induced UCP-1 expression in white adipose tissues, but also further promoted that in olanzapine-medicated rats.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Chromium appears to have a negligible effect on olanzapine-increased food intake, indicating there’s a possibility of increased energy expenditure as an explanation for the improvement in weight gain. Increasing evidence indicates that an increased expression of UCP-1 in white adipose tissues represents an alternative mechanism for the improvement of metabolic impairment via energy expenditure [35]. Here, we found that chromium not only induced UCP-1 expression in white adipose tissues, but also further promoted that in olanzapine-medicated rats.…”
Section: Discussionsupporting
confidence: 64%
“…Apart from being a representative marker of beige/brite or brown adipocytes, thermogenic UCP-1 in white adipose tissues represents an emerging molecule in the regulation of energy metabolism and adipose inflammation [35]. Although there was no significant difference of UCP-1 protein expression in white adipose tissues of olanzapine group, chromium showed promoting effect on UCP-1 protein expression and further augmented UCP-1 expression in olanzapine-medicated rats (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that PVAT respond to thermogenic challenges in a manner consistent with a brown/beige phenotype. Abdominal aortic PVAT experiences a strong browning process in response to cold, as evidenced by increases in multilocular cells and enhanced expressions of UCP1 and PPARγ co‐activator‐1α (PGC‐1α) . Consistently, in mice maintained at thermoneutrality, the expression levels of brown/beige marker genes are repressed in PVAT.…”
Section: Inflammation and The Brown/beige Properties Of Perivascular mentioning
confidence: 92%
“…Consistently, in mice maintained at thermoneutrality, the expression levels of brown/beige marker genes are repressed in PVAT. Moreover, cold exposure significantly reduces the expression of pro‐inflammatory cytokines (TNFα and IL‐6) in the PVAT . In thoracic periaortic PVAT, thermoneutrality enhances macrophage‐mediated inflammation .…”
Section: Inflammation and The Brown/beige Properties Of Perivascular mentioning
confidence: 99%
“…Cold exposure can also stimulate the browning effect on abdominal aortic PVAT in HFD-fed rats by increasing uncoupling protein 1 (UCP-1) and PGC-1α expression levels. Expression levels of TNF-α, IL-6, and p65 are significantly reduced, while phospho-AMPK expression is increased in PVAT with cold exposure [128]. In addition, cold conditions stimulate glucose uptake and triglyceride clearance in adipose tissues, which may also contribute to the modulation of oxidative stress in PVAT [129,130].…”
Section: Restoring Brown-like Pvatmentioning
confidence: 96%